Toward a Learning Society. The Reagan Administration's Adult Literacy Initiative - Bell, T. H.; Department of Education, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Because the Reagan administration believes that the problem of illiteracy must be countered with strong action at all levels of government and education in concert with the private sector, President Reagan announced the Adult Literacy Initiative last September. The initiative, which is based on the premise that the private sector has a keen interest in the promotion of literacy, encourages cooperative efforts by the public and private sectors as well as the recruitment of literacy volunteers. Through the National Institute of Education, the Department of Education will establish the National Adult Literacy Project--a program that will identify model literacy programs and develop and test new literacy materials. To utilize untapped student resources, the Department of Education plans to launch a pilot program in which college work-study students will be employed to teach adults how to read. College students and federal employees alike will be encouraged to serve as literacy volunteers. In addition, the Adult Literacy Initiative will encourage literacy efforts from the following segments of society: state and local officials, minority communities, special education groups, and groups serving disabled persons. (MN)
Educational level discussed: Adult Basic Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Literacy; Adult Reading Programs; Cooperative Planning; Educational Cooperation; Educational Needs; Educational Policy; Government Role; Illiteracy; Literacy Education; Public Policy; School Business Relationship; Special Needs Students; Volunteers; Adult Literacy Initiative; Private Sector -- Reagan Administration; Opinion Papers; Speeches/Meeting Papers